2020
DOI: 10.1111/mpp.12944
|View full text |Cite
|
Sign up to set email alerts
|

Developmentally regulated Arabidopsis thaliana susceptibility to tomato spotted wilt virus infection

Abstract: Tomato spotted wilt virus (TSWV) is one of the most devastating plant viruses and often causes severe crop losses worldwide. Generally, mature plants become more resistant to pathogens, known as adult plant resistance. In this study, we demonstrated a new phenomenon involving developmentally regulated susceptibility of Arabidopsis thaliana to TSWV. We found that Arabidopsis plants become more susceptible to TSWV as plants mature. Most young 3-week-old Arabidopsis were not infected by TSWV. Infection of TSWV in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 62 publications
(75 reference statements)
5
32
0
Order By: Relevance
“…The OD 600 of L (+)opt was adjusted to 1.5, which substantially improved its virus rescue efficiency up to 85‐100%. Inoculation of TZSV and INSV was performed as previously described (Huang et al ., 2020). The inoculated tobacco plants were grown in a growth chamber as described above.…”
Section: Methodsmentioning
confidence: 99%
“…The OD 600 of L (+)opt was adjusted to 1.5, which substantially improved its virus rescue efficiency up to 85‐100%. Inoculation of TZSV and INSV was performed as previously described (Huang et al ., 2020). The inoculated tobacco plants were grown in a growth chamber as described above.…”
Section: Methodsmentioning
confidence: 99%
“…Experiments studying the growing edge of the infection focus are also interesting because the behavior of MP-GFP was different from the behavior of the recombinant MP produced in E. coli, which appeared in cells distant from the injected cell after microinjection (Waigmann et al, 1994). Experiments in which DNA encoding MP-GFP was delivered into cells using low-pressure microprojectile bombardment without injuring the leaf (Crawford and Zambryski, 2000;Crawford and Zambryski, 2001) or MP-2xGFP-encoding plasmid delivered via agroinfiltration (Burch-Smith and Zambryski, 2010) demonstrated that TMV MP, similar to the cucumber mosaic virus 3a MP (Itaya et al, 1997) or the tomato spotted wilt virus NSm MP (Huang et al, 2020), showed autonomy from other viral factors, i.e., could independently move to neighboring cells in the absence of viral RNA, but remained relatively close to the initial cell with the introduced MP-encoding DNA. MP-GFP trafficked to an average of eight (Crawford and Zambryski, 2000) or nine (Crawford and Zambryski, 2001) cells adjacent to the bombarded cell.…”
Section: Mp Is Transiently Synthesized In the Early Stages Of A Produmentioning
confidence: 99%
“…For some viruses transported as virions, the MPs, in addition to forming tubular structures, can apparently perform other functions. For example, tomato spotted wilt virus (TSWV) NSm MP is able to move independently of other viral components from a "0" cell to neighboring healthy cells of a model plant such as A. thaliana [73]. It is also known that MPs of tubule-forming CPMV are capable of transporting vRNPs in the AMV model system [30], which indicates the likelihood of intercellular transport in tubule-forming viruses using both vRNPs and virions [4].…”
Section: Diversity and Heterogeneity Of Viral Mps: General Characteristics And Classificationmentioning
confidence: 99%